FORENSIC PATHOLOGY THEORY & PRACTICE - Faridah Mohd Nor; Nadiawati Abdul Razak (Penerbit Universiti Kebangsaan Malaysia, 2021)
Forensic pathology is an intresting sunject, yet horrifying to some. Nevertheless, it is important to compile a short and concise book for use by medical students, police and law officers to have a grasp of knowledge in forensic pathology. This book is equipped with pectures taken during postmortem for easy recall of the cases.